The future of the scientific paper - Bora Zivkovic (JCOM: Journal of Science Communication, 2008)
Will the use of the Web change the way we produce scientific papers? Science go through cycles, and the development of communication of science reflects the development of science itself. So, new technologies and new social norms are altering the formality of the scientific communication, including the format of the scientific paper. In the future, as PLoS One is experimenting right now, journals will be online hosts for all styles of scientific contributions and ways to link them together, with different people contributing to a body of work and making science more interdisciplinary and interconnected.